If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -8 = 21 + -11x Reorder the terms: -8 + -12x = 21 + -11x Solving -8 + -12x = 21 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -8 + -12x + 11x = 21 + -11x + 11x Combine like terms: -12x + 11x = -1x -8 + -1x = 21 + -11x + 11x Combine like terms: -11x + 11x = 0 -8 + -1x = 21 + 0 -8 + -1x = 21 Add '8' to each side of the equation. -8 + 8 + -1x = 21 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 21 + 8 -1x = 21 + 8 Combine like terms: 21 + 8 = 29 -1x = 29 Divide each side by '-1'. x = -29 Simplifying x = -29
| (x/9)=-7x+8x-100-36 | | 1.2(x-3)+17.25=2.5x | | w=120p+185 | | 5x+28=(2)4x+5 | | 8y-5x=100 | | 14+3x(x+2)=7x | | 3(x-2)-5x=9 | | -7xp=1 | | 2x+14=5x-22 | | p=-25d^2+500d | | 7a=8.2 | | 145g=165 | | -2(n-6)=-14 | | h(t)=20-16r^2+32t | | y=-2x^2+x-3 | | 4x^2-18+3=0 | | 7e+8-10=-20 | | -q+2p=3 | | f(x)=-16x^2+192x | | ln(5x)-ln(5)+3ln(x)=0 | | 14-4x=-6-6(8x+4) | | (100+10)9= | | 2x+1=3+y | | 18.9+c=31.2 | | 5(x+7)=8 | | 21Y-8Y(2)=6Y+1-10 | | 23-7+4(x-1)=11 | | 8y-3y+6=-10 | | x*.10=14.79 | | 27r^3+1=0 | | 19-2x-3=2x+6+x | | 7x-15=2x+10 |